The Role of Cyber Law in The Use of Technology in Mass Media - Asih Handayati (IHSA Institute, 2022)
In the era of convergence, as now, technological changes are developing quite rapidly, so that the desired information can be obtained quickly. In the virtual world, the name Cyber Law is known from the term Cyberspace Law which includes several legal subjects in it by using digital technology that can be utilized by the public at large. The development of human thought towards technological progress has provided many positive aspects for human life, but technological progress has also brought its own problems, especially in the aspect of crime. Technological advances can also be utilized by criminal (cyber) perpetrators in completing evil intentions. The impact or effect of this cyber law is felt by all levels, especially in the world order of the mass media. Where the real world is almost replaced by the virtual world. The presence of the cyber era makes human relations no longer hindered by distance and time. All information and news can be accessed by everyone without any obstacles. This is where a new chapter of life begins and the mass media inevitably flocks into a new world called cyberspace. Therefore, there is a need for a standard that regulates the freedom and use of facilities in cyberspace. Because cyber law is the solution to legal uncertainty in cyberspace.